Library of souls [compact disc, unabridged] - Riggs, Ransom (Riggs, Ransom. Novel of Miss Peregrine's Peculiar Children, 2015)
Jacob, Emma, and Addison travel through time from present-day London to the slums of Victorian England to rescue the other Peculiar Children from a guarded fortress.